Gaming as a Form of Experiential Learning: Career Ready Project—Bloom Virtual Village - Deb Bonfield; Pamela Gauci; Dario Guescini; Jackie Tan; Apostolo Zeno (Journal of Innovation in Polytechnic Education)
George Brown College students, in collaboration with industry partners Baycrest Health Sciences and Microsoft, worked with experts to imagine, design, create, validate and employ simulated field experience models. Under close supervision of George Brown’s faculty from two academic divisions, students converted the field placement experience in long-term care into a simulation gaming solution. Upon completion of this initial pilot, George Brown College will begin to integrate the game in several programs in our Centre for Community Services and Health Sciences. Students worked collaboratively to develop a unique digital experiential learning opportunity.